Advancing Teacher Professional Education in Physical Education: Wearable Technology for Sports Learning in the Digital Era of Generation Z and Alpha - Surya Adi Saputra; Anton Komaini (CV. INSPIRETECH GLOBAL INSIGHT, 2026)
Introduction: The rapid technological advancement in the 21st century has fundamentally transformed educational landscapes, particularly in physical education (PE) where traditional teaching methods are being challenged by the digital nativity of Generation Z and Alpha students. These generations, characterized by their intrinsic relationship with technology, require innovative pedagogical approaches that leverage digital tools for enhanced learning experiences. Purpose of the study: This research investigates the effectiveness of integrating wearable technology into physical education teacher professional development programs, specifically examining its impact on pre-service teachers' competencies and their ability to engage Generation Z and Alpha learners in the digital era. Materials and methods: A mixed-methods study was conducted with 120 pre-service teachers enrolled in the Teacher Professional Education Program (PPG) at Universitas Negeri Malang, Indonesia. Participants were divided into experimental (n=60) and control groups (n=60). The experimental group received comprehensive training in wearable technology integration, including fitness trackers, heart rate monitors, and motion sensors, while the control group followed traditional PE pedagogy. Data collection involved pre- and post-intervention assessments, teaching competency evaluations, student engagement measurements, and qualitative interviews. Results: Statistical analysis revealed significant improvements in the experimental group across multiple dimensions. Pre-service teachers demonstrated enhanced technological pedagogical content knowledge (TPACK) scores (M=4.23, SD=0.52 vs. M=3.41, SD=0.48; p<0.001), improved student engagement rates (78.4% vs. 61.2%; p<0.01), and increased confidence in teaching Generation Z and Alpha students (M=4.15, SD=0.61 vs. M=3.28, SD=0.73; p<0.001). Wearable technology integration showed positive correlations with enhanced motor skill assessment accuracy (r=0.742, p<0.001) and personalized learning delivery (r=0.689, p<0.001). Conclusions: The integration of wearable technology in PE teacher professional education significantly enhances teaching competencies and preparedness for Generation Z and Alpha learners. The findings support the transformation of traditional teacher preparation programs to include technology-enhanced pedagogical approaches that align with contemporary learning preferences and digital nativity characteristics.